Dissolved organic matter and its relationship to macrophytes and fish assemblages in the lower kinabatangan river catchment, sabah, malaysi - Salani Selveno (2009)
Dissolved organic matter (DOM) is an important source of energy, which aquatic organisms rely heavily on for their survival. The significance of DOM toward the aquatic ecology and its influence on aquatic organism like macrophytes and fish assemblages has not been studied in Lower Kinabatangan River (LKR) Catchment, Sabah, Malaysia. This study was carried out from October 2015 till May 2016, at different types of land use; oil palm plantations (OP), secondary forest (SF) and mixed vegetation (MV). A total of 180 water samples were collected to characterize DOM. Spectroscopic analysis was applied to characterize the DOM and interpreted using discriminant analysis (DA). DA of DOM between land use indicates that pH was dominant at MV and dissolved organic carbon (DOC), dissolved nitrogen (DN), terrestrial-like and microbial processed of DOM (peak C & M) with low molecular DOM (ratio of Peak C/a340) were dominant in OP meanwhile absorbance coefficient (a340) indicates allochthonous DOM was dominant in SF. Conversely, temperature, conductivity, DOC, absorption coefficients (a340) and DN showed significant seasonal variation. DOM constituent at OP highly influence with microbial degraded DOM enhanced by DN during wet period while dry period (March 2016) the DOM highly influence with photodegradation enhanced by temperature as exposure of surface water to sunlight. A total of 777 individuals of fish ( 19 species from 11 families) caught using gill nets with mesh size of 50 mm, and macrophytes from 22 families with 25 species were recorded by using line transect and quadrat method in LKR. Subsequently, employment of canonical corresponded analysis (CCA) (Monte Carlo p<0.05) at LKR showed emergent macrophytes at SF significantly associates with humic substances and aromaticity of DOM, in contrast to OP, the free floating invasive species associates positively with high microbial metabolism and low DO concentration. The tolerable fish species able to adapt wider range of DOC concentration meanwhile the peak B and temperature show a negative correlation with Labiobarbus sabanus taxa. The findings suggest that changes in land use and seasonality affect the concentration of DOM in river environment, which in turn causes total alteration to the abundance and diversity of fishes compared to macrophytes.